2013
DOI: 10.1364/oe.21.018361
|View full text |Cite
|
Sign up to set email alerts
|

A study on forward scattering Mueller matrix decomposition in anisotropic medium

Abstract: In this work, we apply Mueller matrix polar decomposition (MMPD) method in a forward scattering configuration on anisotropic scattering samples and look for the physics origin of depolarization and retardance. Using Monte Carlo simulations on the sphere-cylinder birefringence model (SCBM), and forward scattering experiments on samples containing polystyrene microspheres, well-aligned glass fibers and polyacrylamide, we examine in detail the relationship between the MMPD parameters and the microscopic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 21 publications
3
59
0
Order By: Relevance
“…5 and 7. However, since the birefringence of tissues can also be originated from the well aligned cylindrical scatterers [34], we carry on further simulations using the sphere-cylinder scattering model (SCSM) which does not include the birefringent interstitial medium. For the MC simulated results of SCSM shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 7. However, since the birefringence of tissues can also be originated from the well aligned cylindrical scatterers [34], we carry on further simulations using the sphere-cylinder scattering model (SCSM) which does not include the birefringent interstitial medium. For the MC simulated results of SCSM shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that spherical scatterers contribute only to depolarization, not to diattenuation and retardance. 26 We apply 4 × 4 and 3 × 3 decomposition methods to the experimental and simulated Mueller matrices for the spheres with different scattering coefficients and sizes, as shown in Figs. 4(a)-4(c).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] In a recent study, 4 we showed that scattering by well-aligned cylindrical scatterers displayed anisotropic effects, including a retardance that was similar to that of a piece of birefringent media whose extraordinary axis, and the fast axis, was along the axial direction of the aligned cylinders. We also examined the different contributions to the polarization features provided by the well-aligned cylindrical scatterers and the anisotropic interstitial medium.…”
Section: Introductionmentioning
confidence: 84%
“…[4][5][6][7]13 The diameter and density of the spherical and cylindrical scatters, the degree of the alignment and spatial orientation of the cylindrical scatters, the optical properties of the scatterers, and the interstitial media were all variables used in the simulations to mimic the properties of turbid media such as tissues. …”
Section: Monte Carlo Simulations and Scattering Modelmentioning
confidence: 99%
See 1 more Smart Citation